Blimbingsari: Modal Sosial Dan Peran Pemda Dalam Pembangunan Ekonomi Di Kabupaten Jembrana, Bali - I Wayan Ruspendi Junaedi (Universitas Kristen Wira Wacana Sumba, 2013)
Poverty is the biggest problem in the world and also as an enemy for all nations and we have commitment in order to reduce the poverty . In order to reducing the poverty in the country especially in Blimbingsari, the Local Government needs to develop the economy of their own region so that the regions (society/people) have their own welfare. In this paper the researcher, will explain about the role of the Local Government in kabupaten Jembrana, west Bali, Propince of Bali in order to developed the economy especially in Blimbingsari population, Melaya, Jembrana until they create an new entrepreneurs. From that problem and statement above, the researcher make the main research question is that “how the Social Capital of the society and the local government role in order to develop the society economy in Blimbingsari”. From that main research question, the researchr make a research problem in three research question i.e.: (1). what kind of role that the local government do for developing the economic in Blimbingsari? (2). what kind of the social capital that the society do for developing the economic in Blimbingsari? (3). what kind of national program for developing the economic in Jembrana, especially in Blimbingsari? Key word: Development, Poverty, Role, Local Government, and Social Capital